Prediction on import volume of Central Asian gas for stable supply in winter - Linna DENG; Yi DING; Qingguo WU; Xiang ZHOU; Yifan XIANG; Jinwei YANG (You-qi chuyun, 2022)
The Trans-Asia Gas Pipeline is an important onshore energy corridor for China. In the recent winters requiring stable supply, the supply and download volumes of the imported Central Asian gas in the gas source and transit countries fluctuate greatly due to the influence of temperature change, which often leads to the unplanned and unexpected reduction of gas transferred to China. In this case, no measure can be taken in advance, thus affecting China's capacity to ensure the stable supply of gas in winter. In order to solve this problem, the historical data of the factors affecting the supply and download volumes of gas in winters requiring stable supply were analyzed and evaluated, the correlation between the factors was quantified, and a mathematical prediction model with the temperature of the gas source and transit countries of imported Central Asian gas as the independent variable was established to predict the change trend of Central Asian gas transferred to China. In addition, the model is verified to be accurate by comparing the model prediction results with the actual gas volume, and the prediction results could provide support for timely raising of emergency resources in China, which is conductive to effectively controlling the operation and adjusting optimal window period, so as to avoid the loss of energy consumption caused by delayed adjustment of working conditions.